2006
DOI: 10.1369/jhc.5a6871.2006
|View full text |Cite
|
Sign up to set email alerts
|

AM-3K, an Anti-macrophage Antibody, Recognizes CD163, a Molecule Associated with an Anti-inflammatory Macrophage Phenotype

Abstract: CD163 is a member of the scavenger receptor cysteine-rich superfamily restricted to the monocyte/macrophage lineage and is thought to be a useful marker for anti-inflammatory or alternatively activated macrophages. In this study we used mass spectrometric analysis to determine that the antigen recognized by the antibody AM-3K, which we previously generated as a tissue macrophage-specific monoclonal antibody, was CD163. An anti-inflammatory subtype of macrophages stimulated by dexamethasone or interleukin-10 sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
157
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(165 citation statements)
references
References 42 publications
7
157
0
1
Order By: Relevance
“…1A). CD163 has been shown to be associated with an anti-inflammatory MU phenotype, either alternatively activated MU or those tissue MU isolated from patients with granulomatous disease [13]. Our finding that MU2 express CD163 confirms the association of CD163 with antiinflammatory activities.…”
Section: Resultssupporting
confidence: 82%
“…1A). CD163 has been shown to be associated with an anti-inflammatory MU phenotype, either alternatively activated MU or those tissue MU isolated from patients with granulomatous disease [13]. Our finding that MU2 express CD163 confirms the association of CD163 with antiinflammatory activities.…”
Section: Resultssupporting
confidence: 82%
“…Despite the unresolved issue, our novel finding that Nef reduced the expression of CD163 and phagocytic activity of M2-MF (Fig. 6), both of which are characteristics of M2-MF (13,36,51,52), strongly suggests that Nef drives anti-inflammatory M2-MF toward MF with an M1-like phenotype.…”
Section: Discussionmentioning
confidence: 89%
“…6A), the high expression of which is one of the characteristics of M2-MF (51,52). Although the surface expression levels of another scavenger receptor CD204, as well as HLA-DR, were also reduced, the degree was moderate compared with that of CD163 (Fig.…”
Section: Effect Of Soluble Nef and Its Mutants On Phenotypes Of M2-mfmentioning
confidence: 94%
“…24 ). CD68 is considered to be a pan-macrophage marker and CD163 was reported to show promising signs of being a somewhat specific marker of M2 macrophages 31,32 . However, our study suggests these assumptions may not be generally applicable.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CD163-positive macrophages may in some cases outnumber CD68-positive cells 37,41 as indicated by our study. Many reports have used CD163 for identification of M2 macrophages 14,16,17,31,32 . However some studies have suggested, as well as our results, that CD163, being a good marker for TAMs in general, cannot be considered an exclusive marker of M2 macrophages when used on its own 37,38 .…”
Section: Discussionmentioning
confidence: 99%